2017
DOI: 10.3390/s17040839
|View full text |Cite
|
Sign up to set email alerts
|

Fructose and Pectin Detection in Fruit-Based Food Products by Surface-Enhanced Raman Spectroscopy

Abstract: Surface-Enhanced Raman Spectroscopy (SERS) enables the investigation of samples with weak specific Raman signals, such as opaque samples, including fruit juices and pulp. In this paper, biological apple juices and apple/pear pulp have been studied in order to evidence the presence of fructose and pectin, which are components of great relevance for quality assessment of these kinds of products. In order to perform SERS measurements a low-cost home-made substrate consisting of a glass slide decorated with 30-nm-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
(68 reference statements)
0
24
0
1
Order By: Relevance
“…38,40 The amount of sodium citrate was defined in order to obtain GNPs with an expected diameter of about 30 nm since preliminary measurements showed that this was a good choice for SERS applications. 38 Particle size and stability of the resulting preparations were investigated by means of absorption spectroscopy, transmission electron microscope (TEM), and dynamic light scattering (DLS). In particular, absorption spectroscopy was used to obtain information on the plasmon resonance peak and to study the stability of the preparations.…”
Section: Nanoparticle Preparation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…38,40 The amount of sodium citrate was defined in order to obtain GNPs with an expected diameter of about 30 nm since preliminary measurements showed that this was a good choice for SERS applications. 38 Particle size and stability of the resulting preparations were investigated by means of absorption spectroscopy, transmission electron microscope (TEM), and dynamic light scattering (DLS). In particular, absorption spectroscopy was used to obtain information on the plasmon resonance peak and to study the stability of the preparations.…”
Section: Nanoparticle Preparation and Characterizationmentioning
confidence: 99%
“…In general, no features due to the GNPs were present in the 200 to 1800 cm −1 range, which is the region of interest of the present study. 38 For μ-RS measurements, the paper cones with GCF were directly examined. μ-RS was also performed on a pristine paper cone (without GCF) under experimental conditions similar to those used for sampling GCF to distinguish the signal from the substrate contribution.…”
Section: Spectra Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Сучасні знання про патогенез автоімунних захворювань шкіри дали змогу визначити три основні антигенні структури, які є мішенню для імунної відповіді: десмосоми, напівдесмосоми та фібрили [18,26]. Антигенами при даній нозологічній одиниці є трансмембранні глікопротеїни десмосом -десмоглеїни, адгезуючі молекули кадгеринового типу та ін.…”
Section: вступunclassified
“…Final GNP diameter depends on the concentration of sodium citrate, and it is of the order of a few ten of nanometers (about 30 nm, in the case here considered). Details on the fabrication and optical, Dynamic Light Scattering (DLS) and Transmission electron microscopy (TEM) characterization of GNPs are reported in Refs [14,15]. Hydrogen tetrachloroaurate (HAuCl4), and trisodium citrate were purchased from Sigma-Aldrich (Sigma-Aldrich Co., St. Louis, MO, USA).…”
Section: Sers Measurementsmentioning
confidence: 99%